Advanced oxidation treatments of olive mill wastewater - Ivanov, Mia; Perić, Katarina, inženjerka prehrambenog inženjerstva; Štefanac, Tea; Stulić, Višnja; Kraljić, Klara; Smoljanić, Goran; Landeka Dragičević, Tibela; Herceg, Zoran; Vukušić, Tomislava (2019)
New and innovative advanced oxidative processes for wastewater treatments are currently in the focus of scientific research and development for possible industrial implantation. The main aim of this study was to investigate the effect of cold plasma treatment, high intensity ultrasound and UV radiation with the addition of additives: H2O2, TiO2, FeCl3 x 6H2O on degradation and removal of complex organic compounds from olive mill wastewater (OMWW). Olive mill wastewater represents a potential ecological problem when it is raw disposed into the environment, because of its high organic load. OMWW samples (with and without additives) were treated by high-voltage plasma discharge at frequencies 60 Hz and 120 Hz in combination with pumped gases (nitrogen, air and oxygen) for 30 minutes, by UV radiation for 30 minutes and 10 minutes by high intensity ultrasound. Physico-chemical parameters of quality, chemical oxygen demand (COD), and total dissolved carbon (TOC) were determined. The results have shown the efficacy of plasma treatment in degradation of organic compounds as well as degradation and reduction of polyphenolic compounds. Reduction of colour and total dissolved carbon occurred in all treated samples, mostly with the addition of FeCl3 x 6H2O. Treatment with UV radiation and ultrasound proved to be the most efficient resulting in the 50% reduction of organic compounds after a 10-minute treatment.
Bibliografija: str. 77-78.
Summary.
Keywords: Otpadne vode -- Obrada otpadnih voda -- Proizvodnja maslinovog ulja -- Oksidacijske metode